Critical reading of media in school textbooks from the educational communication - Ojeda Sánchez, Ximena (2015)
This article focuses on the results of a research on the concept of critical reading of the media in school coursebooks from seventh grade in primary school to second grade in secondary school, by considering the point of view of the communication and educational areas. The aim is to know the concept of critical reading that is present in the coursebooks given by the Ministry of Education, in order to establish the levels of media alphabetization that are given by the several contents and activities inside the learning resources. The results indicates that the methodology proposed for the teaching of the media’s critical readings in coursebooks focuses on an education “through” the media, by emphasizing the functional and instrumental level of the media in all of the coursebooks that were analyzed.